Measure or perish - Marcos, Mari-Carmen (Anuario ThinkEPI, 2012)
Based on the distinction between the concepts of usability and user experience, three categories of related metrics are identified and described: those that measure observable aspects of website performance, user behavior, and subjective aspects derived from what users report.
Keywords: Usability; User experience; Web metrics; Performance measures; Behavioral metrics.